Improved Profits and Wetland Paddy Farming Scale as the Leading Commodity in Agro ecological Zones - Joko Mulyono; Setia Hadi; Khursatul Munibah (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2016)
This study aims to analyze the feasibility of paddy farming as the leading commodity according agro-ecological zones (AEZ), increase in net profit and the scale of farming. The study was conducted at the location of the paddy fileds as leading commodity and non-leading commodity Bantul Regency in 2015. The feasibility of farming analyzed by revenue and cost ratio (R/C), the increase in profits was analyzed with an increase in net profit (NKB) and the scale of farming analyzed by determining the break even point of production (TIP) or break even point of price (TIH). The results showed that paddy farming as the leading commodity according agro ecological zones in Bantul is feasible and more optimal (R/C 2.17) than the non leading commodity (R/C 1.99). Paddy farming as the leading commodity according agro ecological zones can raise the net profit (NKB 1.13). Paddy farming as the leading commodity according agro ecological zones can provide benefits if the production is at least 2,729 kg/ha or the price is at least Rp. 1,643/kg.